1999
DOI: 10.1017/s0022112099004498
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a drag-reducing surfactant on a turbulent velocity field

Abstract: A two-component laser-Doppler velocimeter, with high spatial and temporal resolution, was used to study how the introduction of a drag-reducing surfactant to water changes the fully-developed velocity field in an enclosed rectangular channel. Measurements were made for four different Reynolds numbers, Re = 13300; 19100; 32000, and 49100 (based on the bulk viscosity, the half-height of the channel, and the viscosity of water). For a fixed volumetric flow the pressure drop was reduced by 62 to 76% when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
74
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 14 publications
14
74
1
Order By: Relevance
“…In case 4, no apparent log-law (i.e., constant ζ) region was found between the elastic layer and the core region. Similar behavior was seen in experimental results (Warholic et al, 1999;, where turbulent motions were suppressed and a nearly maximal level of DR was achieved. Hence, the y e in case 4 could not be given explicitly from the above procedure.…”
Section: Mean Velocity Profilesupporting
confidence: 87%
“…In case 4, no apparent log-law (i.e., constant ζ) region was found between the elastic layer and the core region. Similar behavior was seen in experimental results (Warholic et al, 1999;, where turbulent motions were suppressed and a nearly maximal level of DR was achieved. Hence, the y e in case 4 could not be given explicitly from the above procedure.…”
Section: Mean Velocity Profilesupporting
confidence: 87%
“…These polymers, however, can only be used in liquid flows, and their effect is largely degraded after the fluid has been subjected to very high shear rates, as occurs in pumps. More recent work (e.g., Chara et al 1993;Miska et al 1995;Warholic et al 1999;Zakin 2001) has used very low concentrations of surfactant ions which self-assemble into long-chain micelle structures, and in so doing produce a similar effect as long-chain polymer molecules. Unlike polymers, however, after passing through regions of high shear rates these micelles rapidly reassemble to recover their original effectiveness.…”
Section: Active Sublayer Controlmentioning
confidence: 99%
“…It is known, however, that the flow of DR solutions lacks some of the features of turbulent flow. Studies have shown that radial turbulence intensities are greatly reduced in DR flow [6], and it is accepted that this suppression of radial turbulence results in the reduced pressure loss [7].…”
Section: Introductionmentioning
confidence: 99%